Polidocanol Plus Glucose Versus Glucose Alone for the Treatment of Telangiectasias: Triple Blind, Randomised Controlled Trial (PG3T) - Bertanha, Matheus [UNESP]; Yoshida, Winston B. [UNESP]; Bueno de Camargo, Paula A. [UNESP]; Moura, Regina [UNESP]; Reis de Paula, Dênia [UNESP]; Padovani, Carlos R. [UNESP]; Sobreira, Marcone L. [UNESP] (Elsevier, 2020)
Objective: The aim of this study was to compare the effectiveness and safety of two sclerosing agents used to treat telangiectasias in the lower limbs: 0.2% polidocanol + 70% hypertonic glucose (HG) vs. 75% HG alone. Methods: A prospective, randomised, triple blind, controlled, parallel group trial with patients randomly assigned in a 1:1 ratio between January and December 2015, with a two month follow up, from a single academic medical centre in Brazil, was carried out. Participants were women aged 18–65 years with telangiectasias on the lateral aspect of one thigh, classified as C1EpAsPn who underwent sclerotherapy in a single session with 0.2% polidocanol + 70% HG or 75% HG alone to treat the telangiectasias on an area limited by a rectangular template. The primary effectiveness endpoint was elimination of 75% of the telangiectasias within 60 days vs. the pre-treatment pattern. The length of vessels was measured on images obtained before and after treatment using ImageJ software. Safety outcomes were analysed immediately, 7 days, and 60 days after the treatment, and included pigmentation. Results: A total of 115 patients were included, 98 of whom completed the study. Sclerotherapy with 0.2% polidocanol + 70% HG was significantly more effective than with 75% HG alone to treat telangiectasias in the target area (82.2% vs. 63.9%; p <.001); considering a minimum improvement of 75%, there was a 0.49 risk reduction (95% confidence interval 0.24–0.98; p =.047). No severe adverse events occurred in either group. Pigmentation was the most common minor adverse event and was significantly shorter in length in the group treated with 0.2% polidocanol + 70% HG (median 0 cm vs. 0.5 cm, respectively; p =.033). Conclusion: Polidocanol 0.2% plus 70% HG had better results than 75% HG alone in sclerosing telangiectasias. No severe adverse events occurred. Pigmentation occurred in both groups and was shorter in length in the group treated with 0.2% polidocanol + 70% HG.
Keywords: Glucose solution; Hypertonic; Polidocanol; Sclerosing solutions; Sclerotherapy; Telangiectasias; Veins